“Much the more political of the two”: Mabel FitzGerald and the Irish revolution - Morrissey, C (Taylor and Francis (Routledge), 2016)
This article offers an assessment of the career and ideology of the Irish republican and Cumann na mBan activist Mabel FitzGerald, née McConnell (1884–1958). From a staunchly Unionist Belfast Presbyterian family, Mabel converted to republicanism while an undergraduate in the early 1900s. In 1911 she eloped with Desmond FitzGerald, a Catholic poet. The couple became prominent nationalist activists, and participated in the Easter Rising. In 1922 Desmond, now a minister in the provisional government, supported the Anglo-Irish Treaty. This caused a rift with Mabel, who remained a republican. Although she chose not to separate from her husband, she retained her republican sympathies; there is evidence that she continued to offer aid to the anti-Treaty side. After the Civil War, Mabel and Desmond were reconciled, and she strongly revised her political views, eventually coming to regret the Irish separatist project. Mabel FitzGerald’s career offers insight into the nature of radicalisation among Irish nationalist activists, as well as providing an example of the competing loyalties of family and politics that frequently informed and constrained the actions of nationalist activists.